2008
DOI: 10.5694/j.1326-5377.2008.tb01897.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasive pneumococcal disease in Indigenous people in north Queensland: an update, 2005–2007

Abstract: Objective: To examine trends in invasive pneumococcal disease (IPD) in Indigenous people in north Queensland following the introduction of the 7‐valent pneumococcal conjugate vaccine (7vPCV). Design: Trends in IPD were compared over three 3‐year periods: before the introduction of 7vPCV for Indigenous children (1999–2001), and two consecutive periods after its introduction (2002–2004 and 2005–2007). Main outcome measures: Incidences of IPD in Indigenous children and adults in 1999–2001 and 2005–2007; trends in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…These findings correspond with other research studies that have identified a greater burden of IPD in Aboriginal populations (6, 10, 11). Several studies have cited multiple possible risk factors such as crowded living conditions, socio-economic status, underlying medical conditions and a greater exposure to risks such as smoking (6, 10, 11) as possible explanations.…”
Section: Discussionsupporting
confidence: 92%
“…These findings correspond with other research studies that have identified a greater burden of IPD in Aboriginal populations (6, 10, 11). Several studies have cited multiple possible risk factors such as crowded living conditions, socio-economic status, underlying medical conditions and a greater exposure to risks such as smoking (6, 10, 11) as possible explanations.…”
Section: Discussionsupporting
confidence: 92%
“…This review also found studies of indirect effects of PCV on high-risk populations, including 9 studies evaluating PCV on either VT-NP carriage 9,10,42,43 or VT-IPD 13,17,18,23,28,31 ; no studies evaluated pneumonia and all used 3+1 or 3+PPV23 schedules. Seven studies focused on the impact of PCV on indigenous populations, including Australian Indigenous, Alaskan Native and American Indian populations, and 2 focused on HIV-infected populations.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, rates of IPD caused by serotype 19A in Indigenous children have fluctuated over recent years and serotype 6A became the most common non-vaccine IPD serotype in Indigenous children and the second most common in non-Indigenous children. [3] Hanna[22] compared IPD serotypes in under 5 year old Indigenous children living in far North Queensland pre- and post-7PCV implementation. They concluded that there was no evidence of non-7PCV serotype replacement.…”
Section: Discussionmentioning
confidence: 99%